ASUHAN KEPERAWATAN PADA KLIEN DENGAN EFUSI PLEURA - Arma Lutfiya Yogi Alfian; Kurniawati Kurniawati; Zuliani Zuliani (Jurnal EDUNursing, 2020)
Abstract Pleural effusion is a tern used for fluid accumulation in the pleural cavity. In the normal pleural cavity there is serous fluid with a average amount of 0,1 ml/kg/day (which is in the state of homeostatis there are 5-15 ml of fluid in the pleural movements. The stability of the amount of pleural fluid is regulated though a balance mechanism between transudation of pleura; capillaries and reabsorption by visceral and pariental veins, and lymph nodes. This reserch method of scientific writing is a case study with four patients. This case study literatur a nursing process stage approach that experiences pleural effusion with an ineffective breathing pattern. This conducting nursing literatur study on pleural effusion clients is found diagnosis of an ineffective breath pattern. All clients are resolved, unles one of the client’s Tn. S (46 year) is not resolved due to the attack disease. The achievement of the healing of disease is necessary to evaluate continuously and directed by the record of development, also required knowledge of the regular therapeutic program and management of nursing care with a cooperation between nurses, clients, and other health teams. Keywords: Nursing care, pleural effusion, case study.